Knowledge, Attitude and Practices Towards Foot and Mouth Disease Among Farmers and Veterinary Practitioners in Selected Border Regions of Pakistan Adjoining to Afghanistan - Abdul Kabir; Asghar Ali Kamboh; Muhammad Abubakar; Kanwar Kumar; Abdulkareem Mohammed Matar (Veterinary Medicine and Science, 2025)
ABSTRACT This study was conducted to look into the knowledge, attitudes and practices (KAP) of farmers, animal wholesalers and veterinary practitioners on foot and mouth disease (FMD) in the border area of Pakistan adjoining Afghanistan. Nearly half (41%) of the farmers understood the name of the disease or were aware of its incidence in their neighbourhood. The majority of farmers were able to identify the clinical signs (77.9% salivation, 74% tongue ulcers, 73.4% gum lesions, 71% hoof lesions) of FMD in their livestock. Over half of the farmers (54%) preferred not to purchase cattle from unidentified or potentially contaminated sources to stop the spread of FMD. The majority of farmers (61%) claimed that the ‘introduction of new animals’ was the main reason the illness appeared on their farms. The extent of the animal wholesalers' clinical knowledge was restricted to identifying salivation and lesions in the mouth and on the feet as signs of the disease. Eighty‐three percent of local veterinarians reported the prevalence of FMD to the provincial, regional and central veterinary authorities. More than half of them (71%) kept records of the animal diseases seen and/or treatment plans implemented. In the border region between Pakistan with Afghanistan, there is no ongoing formal FMD immunization programme. According to the majority of veterinary practitioners (63%), the main obstacles to FMD control in the area were thought to be poor import restrictions and no quarantine of livestock. Farmers and wholesalers need to have their knowledge gaps filled to reduce the burden of illness in the border region.